Air-stable fluorine ion solid electrolyte as well as preparation method and application thereof

By mixed with +2 -valent metal cations in rare earth fluoride, it improves the ion conductivity and air stability of fluorine ion solid electrolytes, solve the problem of low conductivity and stability of existing materials, and achieve more efficient battery performance.

CN119381536APending Publication Date: 2025-01-28GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661725.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing solid electrolyte materials of fluoride ion battery have low ion conductivity at room temperature and poor air stability, which cannot meet the application requirements of fluoride ion batteries.

Method used

By mixed with+2 metal cations in rare earth fluoride, such as BA, the solid electrolyte of Rexa1-XF3-X and/or REXA1-XF2X+2 is formed to improve its ionic conductivity and air stability.

Benefits of technology

The high -chamber temperature ion conductivity, good air stability and low activation energy of solid -state electrolyte are realized, and their application prospects in fluorite batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381536A_ABST
    Figure CN119381536A_ABST
Patent Text Reader

Abstract

The invention provides an air-stable fluorine ion solid electrolyte and a preparation method and application thereof, the air-stable fluorine ion solid electrolyte comprises RexA1-xF3-x and / or RexA1-xF2x + 2, Re comprises any one or a combination of at least two of rare earth elements, A comprises + 2 valence metal cations, and x is greater than 0 and less than 1. The air-stable fluorine ion solid electrolyte disclosed by the invention has relatively high room-temperature ionic conductivity, good air stability and low activation energy, and has relatively high application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to an air-stable fluoride ion solid electrolyte and a preparation method and application thereof. Background Art

[0002] In the past few decades, with the rapid development of electronic devices, renewable energy and electric vehicles, the importance of energy storage technology has increased. As the current mainstream secondary battery technology, lithium-ion batteries (LIBs) have dominated the market due to their excellent energy density, power density and long life. However, with the increasing demand for higher energy density, higher safety and longer life, the limitations of LIBs have gradually emerged. For example, the scarcity and price volatility of lithium resources, as well as the safety hazards of LIBs under high temperature and high pressure conditions, have prompted researchers to explore new battery chemistries.

[0003] In this context, all-solid-state fluoride ion batteries (FIBs) as a new energy storage technology have attracted widespread attention due to their potential ultra-high energy density and good safety. - It is a new type of energy storage battery system for charge transfer ions. F is the element with the strongest electronegativity (3.98) and the lightest halogen. Its anion (F - ) has good chemical stability, which makes FIBs have a wider electrochemical stability window. - It has a lower degree of solvation than cations of the same charge and thus has better mobility. More importantly, F - The monovalent nature of BiF3 and CuF2 allows electrodes to store multiple F - , making the theoretical energy density as high as 5000Wh L -1 .

[0004] However, the research on FIBs is still in its early stages and still faces some key challenges. For example, suitable solid electrolyte materials have not yet been developed. The solid electrolyte material needs to have both high ionic conductivity and excellent chemical stability. In addition, due to the relatively strong lattice interaction of F- ions, the ion migration ability is limited, resulting in low ionic conductivity of FIBs at room temperature, which limits its practical application.

[0005] Therefore, the research on FIBs solid electrolytes, especially the exploration of fluoride solid electrolyte materials with high ionic conductivity and stability, has become the focus and difficulty of current research. However, the solid electrolyte materials currently studied have low ionic conductivity at room temperature and poor air stability, which cannot meet the requirements of fluoride ion batteries. At present, the room temperature ionic conductivity of some fluoride ion solid electrolytes can reach 10-4 S cm -1 , but the preparation conditions are relatively harsh, and there is still a huge gap in achieving true commercial application.

[0006] Based on the above research, it is necessary to provide a solid electrolyte, which not only has high air stability but also has high room temperature ionic conductivity. Summary of the invention

[0007] The purpose of the present invention is to provide an air-stable fluoride ion solid electrolyte and a preparation method and application thereof. The air-stable fluoride ion solid electrolyte has high room temperature ionic conductivity, good air stability and low activation energy, and has high application prospects.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides an air-stable fluoride ion solid electrolyte, the air-stable fluoride ion solid electrolyte comprising Re x A 1-x F 3-x and / or Re x A 1-x F 2x+2 , wherein Re includes any one or a combination of at least two of the rare earth elements, A includes a +2-valent metal cation, and 0<x<1.

[0010] In the present invention, the ionic conductivity of the material can be improved by doping rare earth fluoride with +2-valent metal cations. The +2-valent metal cation doping will bring about fluorine vacancies, and the vacancies are evenly distributed, and continuous and numerous conduction channels can be formed. Therefore, the ionic conductivity of the solid electrolyte can be improved, and the solid electrolyte can also have good air stability and low activation energy.

[0011] The rare earth elements are Sc, Y and lanthanide elements, wherein the lanthanide elements include any one or a combination of at least two of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium or lutetium, Re x A 1-x F 2x+2 The heat in it is tetravalent.

[0012] The 0<x<1 can be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.99, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, and preferably 0.9≤x<1.

[0013] The +2-valent metal cations described in the present invention are not easy to be over-doped. When the doping content is too high, the formed vacancies will be larger, the conduction channels will be reduced, and the ion transmission rate will be reduced. Therefore, it is preferred that x adopts a specific range.

[0014] Preferably, the Re comprises a combination of at least two rare earth elements, wherein the molar ratio of any two rare earth elements is (0.1-0.8):(0.1-0.8), for example, it can be 0.1:0.8, 0.2:0.7, 0.3:0.6, 0.4:0.5, 0.5:0.4, 0.6:0.3, 0.7:0.2 or 0.8:0.1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the Re comprises La and Ce in a molar ratio of (0.1-0.8):(0.1-0.8), for example, it can be 0.1:0.8, 0.8:0.1, 0.2:0.7, 0.3:0.6, 0.4:0.5, 0.5:0.4 or 0.6:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] The rare earth elements in the solid electrolyte described in the present invention may include a combination of more than two elements, and the present invention preferably has two elements with certain properties and atomic radius differences, and within a specific content range, the lattice can be further optimized to make the vacancies of the material more uniform and the properties of the material more stable.

[0017] Preferably, the A includes any one of Ba, Ca, Mg or Sr or a combination of at least two thereof, preferably Ba.

[0018] The preferred +2-valent metal cation of the present invention is Ba, which has a higher degree of bonding with rare earth elements, which is beneficial to improving the ionic conductivity and stability of the solid electrolyte.

[0019] Preferably, the room temperature ionic conductivity of the air-stable fluoride ion solid electrolyte is greater than 10 -4 S cm -1 , for example, it can be 1×10 -4 S cm -1 , 1.5×10 -4 S cm -1 , 2×10 -4 S cm -1 , 2.5×10 -4 S cm -1 , 3×10 -4 S cm -1 or 4×10 -4 S cm -1, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0020] In a second aspect, the present invention provides a method for preparing the air-stable fluoride ion solid electrolyte as described in the first aspect, the preparation method comprising the following steps:

[0021] AF2 and rare earth fluoride are mixed according to the formula amount to obtain the air-stable fluoride ion solid electrolyte.

[0022] The preparation method of the air-stable fluoride ion solid electrolyte of the present invention is simple, and only requires mixing AF2 and rare earth fluoride, and can be produced and applied on a large scale.

[0023] Preferably, the mixing method comprises ball milling.

[0024] Preferably, the ball milling includes continuous ball milling and intermittent ball milling.

[0025] Preferably, during the ball milling, intermittent ball milling is performed every 1.5-2.5 hours, for example, 1.5 hours, 2.0 hours or 2.5 hours, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] During the ball milling process, the present invention performs intermittent ball milling at regular intervals, thereby improving the ball milling effect.

[0027] Preferably, the ball milling time is 12-16 hours, for example, 12 hours, 14 hours or 16 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the rotation speed of the ball mill is 300-500 rpm, for example, 300 rpm, 400 rpm or 500 rpm, and the ball-to-material mass ratio is (18-22):1, for example, 18:1, 20:1 or 22:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0030] According to the formula, AF2 and rare earth fluoride are ball-milled for 12-16 hours at 300-500 rpm and a ball-to-material mass ratio of (18-22):1, wherein intermittent ball milling is performed every 1.5-2.5 hours during ball milling to obtain the air-stable fluoride ion solid electrolyte.

[0031] In a third aspect, the present invention provides a secondary battery, comprising the air-stable fluoride ion solid electrolyte as described in the first aspect, or comprising the air-stable fluoride ion solid electrolyte prepared by the preparation method as described in the second aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] In the present invention, the ionic conductivity of the material can be improved by doping rare earth fluoride with +2-valent metal cations. The +2-valent metal cation doping will bring about fluorine vacancies, and the vacancies are evenly distributed, and continuous and numerous conduction channels can be formed. Therefore, the ionic conductivity of the solid electrolyte can be improved, and the solid electrolyte can also have good air stability and low activation energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The X-ray diffraction pattern of the solid electrolyte provided in Example 1 of the present invention;

[0035] Figure 2 This is a test curve of ionic conductivity of the solid electrolyte provided in Example 1 of the present invention;

[0036] Figure 3 This is an activation energy test curve of the solid electrolyte provided in Example 1 of the present invention;

[0037] Figure 4 This is the XRD pattern of the solid electrolyte prepared under argon atmosphere in Example 1-1 of the present invention;

[0038] Figure 5 The XRD pattern of the solid electrolyte prepared in Example 1-1 of the present invention after being placed in water and dried;

[0039] Figure 6 The X-ray diffraction pattern of the solid electrolyte provided in Example 2 of the present invention;

[0040] Figure 7 The solid electrolyte ion conductivity test curve provided in Example 2 of the present invention;

[0041] Figure 8 The X-ray diffraction pattern of the solid electrolyte provided in Example 3 of the present invention;

[0042] Fig. 9 The solid electrolyte ion conductivity test curve provided in Example 3 of the present invention;

[0043] Fig.10 The X-ray diffraction pattern of the solid electrolyte provided by Example 4 of the present invention;

[0044] Fig.11This is a test curve of ionic conductivity of the solid electrolyte provided in Example 4 of the present invention;

[0045] Fig.12 The X-ray diffraction pattern of the solid electrolyte provided in Example 5 of the present invention;

[0046] Fig.13 This is a test curve of ionic conductivity of the solid electrolyte provided in Example 5 of the present invention;

[0047] Fig.14 The X-ray diffraction pattern of the solid electrolyte provided by Example 6 of the present invention;

[0048] Fig.15 This is a test curve of ionic conductivity of the solid electrolyte provided in Example 6 of the present invention;

[0049] Fig.16 This is an activation energy test curve of the solid electrolyte provided in Example 6 of the present invention;

[0050] Fig.17 The X-ray diffraction pattern of the solid electrolyte provided in Example 7 of the present invention;

[0051] Fig.18 This is a test curve of ionic conductivity of the solid electrolyte provided in Example 7 of the present invention;

[0052] Fig.19 The X-ray diffraction pattern of the solid electrolyte provided in Example 8 of the present invention;

[0053] Fig. 20 This is a test curve of ionic conductivity of the solid electrolyte provided in Example 8 of the present invention;

[0054] Fig.21 This is a test curve of the ionic conductivity of the solid electrolyte provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.9 Ba 0.1 F 2.9 ;

[0058] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0059] In an air atmosphere, 3 g of barium fluoride and lanthanum fluoride were weighed according to a molar ratio of La:Ba:F of 0.9:0.1:2.9, and then 60 g of zirconia balls were weighed and placed in a zirconia ball milling jar. The weighed fluoride powder (mass of 3 g) was transferred into the ball milling jar and ball milled for 16 hours in a planetary ball mill at a speed of 400 rpm and a ball-to-material ratio of 20:1. During the ball milling, intermittent ball milling was performed every 2 hours to obtain La 0.9 Ba 0.1 F 2.9 ;

[0060] The XRD pattern of the air-stable fluoride ion solid electrolyte is as follows: Figure 1 shown.

[0061] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 1 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. The ionic conductivity test curve is shown in Figure 2 The results show that at room temperature, the fluoride ion conductivity is 2.81×10 -5 S cm -1 , indicating that the fluoride ion solid electrolyte provided in Example 1 has good ionic conductivity at room temperature; in addition, the activation energy test curve is as follows Figure 3 As shown, Figure 3 As shown, its activation energy is 0.22 eV.

[0062] Example 1-1

[0063] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.9 Ba 0.1 F 2.9 ;

[0064] The preparation method of the air-stable fluoride ion solid electrolyte is the same as that of Example 1 except that it is carried out in an argon atmosphere.

[0065] In order to verify the air stability of the material, the same solid electrolyte as in Example 1 was prepared under a complete argon atmosphere. Figure 4 As shown, the XRD patterns of the samples after being placed in water for a period of time and then dried in air are compared. Figure 5 As shown, it can be seen that the composition of the material has not changed significantly.

[0066] Example 2

[0067] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.6 Ba 0.4 F 2.6 ;

[0068] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0069] In an air atmosphere, 3 g of barium fluoride and lanthanum fluoride were weighed according to a molar ratio of La:Ba:F of 0.6:0.4:2.6, and then 54 g of zirconia balls were weighed and placed in a zirconia ball mill. The weighed fluoride powder (mass of 3 g) was transferred into the ball mill and ball milled for 16 hours at a speed of 500 rpm and a ball-to-material ratio of 18:1. Intermittent ball milling was performed every 1.5 hours to obtain La 0.6 Ba 0.4 F 2.6 The XRD pattern of the air-stable fluoride ion solid electrolyte described in this embodiment is as follows: Figure 6 shown.

[0070] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 1 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. The ionic conductivity test curve is shown in Figure 7 The results show that at room temperature, the fluoride ion conductivity is 7.33×10 -6 S cm -1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature.

[0071] Example 3

[0072] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.2 Ba 0.1 Ce 0.7 F 2.9 ;

[0073] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0074] In an air atmosphere, 3 g of barium fluoride, lanthanum fluoride and lanthanum fluoride were weighed according to the molar ratio of La:Ba:Ce:F of 0.2:0.1:0.7:2.9, and then 66 g of zirconia balls were weighed and put into a zirconia ball milling jar. The weighed fluoride powder (mass of 3 g) was transferred into the ball milling jar and ball milled for 14 hours at a speed of 300 rpm and a ball-to-material ratio of 22:1. Intermittent ball milling was performed every 2.5 hours to obtain La 0.2 Ba 0.1 Ce 0.7 F 2.9 .

[0075] The XRD pattern of the air-stable fluoride ion solid electrolyte described in this embodiment is as follows: Figure 8 shown.

[0076] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 0.97 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. The ionic conductivity test curve is shown in Fig. 9 The results show that at room temperature, the fluoride ion conductivity is 4.32×10 -4 S cm -1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature.

[0077] Example 4

[0078] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.8 Ba 0.1 Ce 0.1 F 2.9 ;

[0079] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0080] In an air atmosphere, 3 g of barium fluoride, lanthanum fluoride and lanthanum fluoride were weighed according to the molar ratio of La:Ba:Ce:F of 0.8:0.1:0.1:2.9, and then 60 g of zirconia balls were weighed and put into a zirconia ball milling jar, and the weighed fluoride powder (mass of 3 g) was transferred into the ball milling jar, and ball milled for 16 hours at a speed of 400 rpm and a ball-to-material ratio of 20:1, wherein intermittent ball milling was performed every 2 hours to obtain La 0.8 Ba 0.1 Ce 0.1 F 2.9 .

[0081] The XRD pattern of the air-stable fluoride ion solid electrolyte described in this embodiment is as follows: Fig.10 shown.

[0082] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 1 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. The ionic conductivity test curve is shown in Fig.11 The results show that at room temperature, the fluoride ion conductivity is 1.35×10 -5 S cm -1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature.

[0083] Example 5

[0084] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.6 Ba 0.1 Ce 0.3 F 2.9 ;

[0085] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0086] In an air atmosphere, 3 g of barium fluoride, lanthanum fluoride and lanthanum fluoride were weighed according to the molar ratio of La:Ba:Ce:F of 0.6:0.1:0.3:2.9, and then 60 g of zirconia balls were weighed and put into a zirconia ball milling jar, and the weighed fluoride powder (mass of 3 g) was transferred into the ball milling jar, and ball milled for 16 hours at a speed of 400 rpm and a ball-to-material ratio of 20:1, wherein intermittent ball milling was performed every 2 hours to obtain La 0.6 Ba 0.1 Ce 0.3 F 2.9 .

[0087] See also Fig.12 , Fig.12 This is the X-ray diffraction pattern of the electrolyte powder prepared in Example 5 of the present invention.

[0088] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 0.99 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. Fig.13 , Fig.13 The electrolyte ion conductivity test curve provided in Example 5 of the present invention shows that the fluoride ion conductivity is 2.19×10 -4 S cm-1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature.

[0089] Example 6

[0090] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.4 Ba 0.1 Ce 0.5 F 2.9 ;

[0091] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0092] In an air atmosphere, 3 g of barium fluoride, lanthanum fluoride and lanthanum fluoride were weighed according to a molar ratio of La:Ba:Ce:F of 0.4:0.1:0.5:2.9, and then 60 g of zirconia balls were weighed and put into a zirconia ball milling jar. The weighed fluoride powder (mass of 3 g) was transferred into the ball milling jar and ball milled for 16 hours at a speed of 400 rpm and a ball-to-material ratio of 20:1, wherein intermittent ball milling was performed every 2 hours to obtain La 0.4 Ba 0.1 Ce 0.5 F 2.9 .

[0093] See also Fig.14 , Fig.14 This is the X-ray diffraction pattern of the electrolyte powder prepared in Example 6 of the present invention.

[0094] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 0.98 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. Fig.15 , Fig.15 The electrolyte ion conductivity test curve provided in Example 6 of the present invention shows that the fluoride ion conductivity is 3.87×10 -4 S cm -1 . It shows that the fluoride ion solid electrolyte provided in this embodiment has good ion conductivity at room temperature;

[0095] In addition, the activation energy of Inventive Example 6 was tested, as shown in Fig.16 As shown, its activation energy is 0.212 eV.

[0096] Example 7

[0097] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is Ce0.9 Ba 0.1 F 2.9 ;

[0098] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0099] In an air atmosphere, 3 g of barium fluoride and cerium fluoride were weighed according to a molar ratio of Ce:Ba:F of 0.9:0.1:2.9, and then 60 g of zirconia balls were weighed and placed in a zirconia ball mill. The weighed fluoride powder (mass of 3 g) was transferred into the ball mill and ball milled for 12 hours at a speed of 400 rpm and a ball-to-material ratio of 20:1. Intermittent ball milling was performed every 2 hours to obtain Ce. 0.9 Ba 0.1 F 2.9 .

[0100] See also Fig.17 , Fig.17 This is the X-ray diffraction pattern of the electrolyte powder prepared in Example 7 of the present invention.

[0101] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 0.95 mm at a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. Fig.18 , Fig.18 The electrolyte ion conductivity test curve provided in Example 7 of the present invention shows that the fluoride ion conductivity is 2.68×10 -4 S cm -1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature.

[0102] Example 8

[0103] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.8 Sr 0.1 Ce 0.1 F 2.9 ;

[0104] The method for preparing the air-stable fluoride ion solid electrolyte comprises the following steps:

[0105] In an air atmosphere, strontium fluoride, lanthanum fluoride and lanthanum fluoride with a total mass of 3g were weighed according to the molar ratio of La:Sr:Ce:F of 0.8:0.1:0.1:2.9, and then 60g of zirconia balls were weighed and put into a zirconia ball milling jar, and the weighed fluoride powder (mass of 3g) was transferred into the ball milling jar, and ball milled for 16 hours at a speed of 400 rpm and a ball-to-material ratio of 20:1, wherein intermittent ball milling was performed every 2 hours to obtain La 0.8 Sr 0.1 Ce 0.1 F 2.9 .

[0106] See also Fig.19 , Fig.19 This is the X-ray diffraction pattern of the electrolyte powder prepared in Example 8 of the present invention.

[0107] After obtaining the electrolyte material, 300 mg of powder was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 1 mm at a pressure of 500 MPa. The ionic conductivity of the electrolyte material was obtained by measuring the AC impedance at room temperature. Fig. 20 , Fig. 20 The electrolyte ion conductivity test curve provided in Example 8 of the present invention shows that the fluoride ion conductivity is 4.72×10 -5 S cm -1 , indicating that the fluoride ion solid electrolyte provided in this embodiment has good ionic conductivity at room temperature

[0108] Example 9

[0109] This embodiment provides an air-stable fluoride ion solid electrolyte, wherein the air-stable fluoride ion solid electrolyte is La 0.1 Ba 0.1 Ce 0.8 F 2.9 ;

[0110] The preparation method of the air-stable fluoride ion solid electrolyte is the same as that of Example 3 except that the raw materials are changed in the formula. In the test results, the fluoride ion conductivity is 3.95×10 -5 S cm -1 .

[0111] Comparative Example 1

[0112] This comparative example provides a fluoride ion solid electrolyte, which is LaF3;

[0113] The ionic conductivity test curve of the solid electrolyte provided in this comparative example is as follows Fig.21 shown.

[0114] 300 mg of the solid electrolyte obtained in the above embodiment and comparative example 1 was weighed into a mold and pressed into a disc with a diameter of 10 mm and a thickness of 1 mm under a pressure of 500 MPa. The AC impedance was tested at room temperature to obtain the ionic conductivity of the electrolyte material. The room temperature ionic conductivity obtained by the test is shown in Table 1:

[0115] Table 1

[0116]

[0117]

[0118] From Table 1 we can see that:

[0119] (1) It can be seen from Comparative Example 1 and Examples 1 and 2 that excessive Ba doping content cannot promote the ion transmission rate, and different doping contents will also have a certain impact on the structure of the material.

[0120] (2) It can be seen from Examples 1-7 and 9 that the ionic conductivity of double rare earth elements is higher than that of a single rare earth element, and that different contents of double rare earth elements also have a certain influence on the ionic conductivity of the material. This is because the two elements have certain differences in properties and atomic radius, which will lead to further optimization of the material's lattice, making the material's vacancies more uniform and the material's properties more stable. The preferred molar ratio of La to Ce in the present invention is (0.2-0.6):(0.3-0.7).

[0121] (3) It can be seen from Examples 4 and 8 that different doped divalent metal cations also have a certain influence on the ionic conductivity of the material, which is mainly related to the degree of combination of the divalent metal cations and the combined rare earth elements, as well as their properties.

[0122] (4) Combining all the examples, it can be seen that the law of the material ion conductivity is: as the Ce content increases, the ion conductivity first decreases, then increases, and then decreases. This is mainly because the change in Ce content will change the lattice structure of the material. The change in the lattice structure will affect the migration path and migration energy barrier of ions in the solid electrolyte. When the Ce content is moderate, a lattice structure that is more conducive to ion migration will be formed, while when the Ce content is too much or too little, it is not conducive to ion migration.

[0123] In addition, Ce and La have different ionic radii, and the increase of Ce will change the ionic size matching in the lattice and affect the diffusion of ions. When the Ce content is moderate, the optimal ionic size matching may be achieved, thereby improving the conductivity.

[0124] In summary, the present invention provides an air-stable fluoride ion solid electrolyte and a preparation method and application thereof. The air-stable fluoride ion solid electrolyte has high room temperature ionic conductivity, good air stability and low activation energy, and has high application prospects.

[0125] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An air-stable fluoride ion solid electrolyte, characterized in that: The air-stable fluoride ion solid electrolyte comprises Re x A 1-x F 3-x and / or Re x A 1-x F 2x+2 , wherein Re includes any one or a combination of at least two of the rare earth elements, A includes a +2-valent metal cation, and 0<x<1.

2. The air-stable fluoride ion solid electrolyte according to claim 1, characterized in that: 0.9≤x<1; Preferably, the Re comprises a combination of at least two rare earth elements, wherein the molar ratio of any two rare earth elements is (0.1-0.8):(0.1-0.8); Preferably, the Re includes La and Ce in a molar ratio of (0.1-0.8):(0.1-0.8).

3. The air-stable fluoride ion solid electrolyte according to claim 1 or 2, characterized in that: The A includes any one of Ba, Ca, Mg or Sr or a combination of at least two of them, preferably Ba.

4. The air-stable fluoride ion solid electrolyte according to any one of claims 1 to 3, characterized in that: The room temperature ionic conductivity of the air-stable fluoride ion solid electrolyte is >10 -4 S cm -1 .

5. A method for preparing the air-stable fluoride ion solid electrolyte according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: AF2 and rare earth fluoride are mixed according to the formula amount to obtain the air-stable fluoride ion solid electrolyte.

6. The preparation method according to claim 5, characterized in that: The mixing is carried out in an air atmosphere; Preferably, the mixing method includes ball milling; Preferably, the ball milling includes continuous ball milling and intermittent ball milling.

7. The preparation method according to claim 6, characterized in that: During the ball milling, intermittent ball milling is performed every 1.5-2.5 hours.

8. The preparation method according to claim 6 or 7, characterized in that: The ball milling time is 12-16h; Preferably, the rotation speed of the ball mill is 300-500 rpm, and the ball-to-material mass ratio is (18-22):

1.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: According to the formula, AF2 and rare earth fluoride are ball-milled for 12-16 hours at 300-500 rpm and a ball-to-material mass ratio of (18-22):1, wherein intermittent ball milling is performed every 1.5-2.5 hours during ball milling to obtain the air-stable fluoride ion solid electrolyte.

10. A secondary battery, characterized in that: The secondary battery comprises the air-stable fluoride ion solid electrolyte as claimed in any one of claims 1 to 4, or comprises the air-stable fluoride ion solid electrolyte prepared by the preparation method as claimed in any one of claims 5 to 9.